2018
DOI: 10.4103/1319-2442.235171
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced acute interstitial nephritis: Prospective randomized trial comparing oral steroids and high-dose intravenous pulse steroid therapy in guiding the treatment of this condition

Abstract: The most important aspect of treating drug-induced acute interstitial nephritis (AIN) is timely discontinuation of the offending drug. Steroids, oral as well as intravenous (IV), are used in the treatment of drug-induced AIN. The present study was undertaken to compare the efficacy of oral prednisolone versus IV suprapharmacological doses of corticosteroids in the treatment of drug-induced AIN. This prospective randomized controlled study included drug-induced AIN diagnosed on histopathology over a period of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 2 publications
0
15
0
2
Order By: Relevance
“…A prospective randomized trial of 31 patients with drug-associated AIN compared the use of 1 mg/kg per day prednisone equivalent with or without an initial bolus of 30 mg/kg methylprednisolone (maximum 1 g). Patients randomized to the pulse dose arm demonstrated a slightly greater improvement in kidney function by 1 week, but by weeks 2 and 3 the degree of recovery from baseline was similar between groups (13). In a multicenter cohort of 182 cases of steroid-treated drug-associated AIN, no benefit was observed with the use of pulse-dose steroids or extended steroid courses.…”
Section: Managementmentioning
confidence: 81%
“…A prospective randomized trial of 31 patients with drug-associated AIN compared the use of 1 mg/kg per day prednisone equivalent with or without an initial bolus of 30 mg/kg methylprednisolone (maximum 1 g). Patients randomized to the pulse dose arm demonstrated a slightly greater improvement in kidney function by 1 week, but by weeks 2 and 3 the degree of recovery from baseline was similar between groups (13). In a multicenter cohort of 182 cases of steroid-treated drug-associated AIN, no benefit was observed with the use of pulse-dose steroids or extended steroid courses.…”
Section: Managementmentioning
confidence: 81%
“…The management of drug-induced AIN typically involves discontinuation of the offending agent [18]. The role of steroid treatment in drug-induced AIN remains controversial, and its efficacy has not been tested in randomized trials [19].…”
Section: Discussionmentioning
confidence: 99%
“…Chowdry et al reported no difference in outcome between the use of IV versus oral steroids, as both are equally effective when used early. More severe complications, however, such as an increase in blood pressure was more apparent in the IV steroid group [18]. There is no definitive guideline regarding the duration of steroid therapy in the treatment of drug-induced AIN.…”
Section: Discussionmentioning
confidence: 99%
“…En las causas autoinmunes, la evaluación sistémica del paciente y el manejo inmunosupresor guiado es clave para el control de la enfermedad. En todos los casos la correcta reanimación hídrica del paciente es imprescindible (45) .…”
Section: Tratamiento De La Ntiaunclassified